On literary worlds - Hayot, Eric, 1972- (New York ; Oxford : Oxford University Press, 2012)
'On Literary Worlds' develops new strategies and perspectives for understanding aesthetic worlds.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Literature -- Aesthetics